1999
DOI: 10.1677/joe.0.1610167
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin receptor subtype expression in cells of the rat immune system during adjuvant arthritis

Abstract: Somatostatin is a neuropeptide that is widely distributed throughout the body. It acts as a neurohormone and a neurotransmitter and may also have an immunomodulatory role. The genes for five subtypes of somatostatin receptors (sst) have been cloned, suggesting that the diverse effects of the peptide might be mediated by different receptors.We are interested in studying the role of sst in inflammation, using an animal model. Because of the up-regulation of sst expression in inflamed joints in human rheumatoid a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 28 publications
3
28
1
Order By: Relevance
“…In the lung, they have been detected on lymphocytes and also on the sensory nerve terminals (13). Somatostatin receptor autoradiography has shown upregulation of somatostatin binding sites in several immunemediated diseases (36,48,49). Furthermore, plasma somatostatin level has been shown to significantly increase during the development of adjuvant-induced arthritis in the rat (16) and, according to the present results, also during endotoxininduced airway inflammation in the mouse.…”
Section: Discussionsupporting
confidence: 73%
“…In the lung, they have been detected on lymphocytes and also on the sensory nerve terminals (13). Somatostatin receptor autoradiography has shown upregulation of somatostatin binding sites in several immunemediated diseases (36,48,49). Furthermore, plasma somatostatin level has been shown to significantly increase during the development of adjuvant-induced arthritis in the rat (16) and, according to the present results, also during endotoxininduced airway inflammation in the mouse.…”
Section: Discussionsupporting
confidence: 73%
“…In addition, histological studies in this model have revealed reduction of lymphocyte infiltration in the synovium and reduced vasculitis in SRIF-treated animals. In our studies we did not observe a reduction in the severity of rat adjuvant arthritis using the SRIF analogue octreotide (ten Bokum et al, 1999b). Takeba et al has shown that SRIF at physiological concentrations inhibits the in vitro proliferation of fibroblast-like synovial cells from RA patients (Takeba et al, 1997).…”
Section: Small-molecule Ghs Has a Considerable Immune-enhancing Effeccontrasting
confidence: 62%
“…Mice and humans express ®ve different receptors for SST (SSTR 1±5 ), each encoded by separate genes (12). We showed that whole unfractionated granuloma cells, as well as T cells (Thy1.2+ or CD4+) isolated from granulomas of schistosome-infected mice, express mRNA only for SSTR 2 (5,13 (14).…”
Section: Sstr Subtype Expression In Murine Granulomasmentioning
confidence: 92%